The Dynamics of the Constellation in East Asia: Japan's Response towards Changes of the Regional Status-quo Post-Panmunjom Declaration - Satwika Paramasatya; Yemima Galih Pradipta (President University, 2019)
Security is an important aspect for a state. In particular, regional security plays important role in influencing state policies and actions. This paper departs from the High Level meeting between South Korea and North Korea in April 2018 which then produces an output in the form of peace agreement, the Panmunjom Declaration. The declaration has different impact to Japan, because it becomes the turning point of the status-quo in the East Asia region. Relations between states are generally driven and motivated by interests rather than the shared identity. This paper aims to analyze the actions and responses of Japan as a pacifist state towards the changes in the constellation of East Asia relations after the Panmunjom Declaration. In the end of this paper, it is concluded that what happened in the East Asia region is accordance to the concept of classical realism theory. The Panmunjom Declaration surely is an international event marked as turning point of East Asia regional status-quo, but could not be claimed as the main factor to drive Japan revising article 9. However, Japan's alertness towards North Korea remains same. Even though it is not the main factor, but the Panmunjom Declaration made Japan interprets its position differently in East Asia, and has influenced Shinzo Abe's narrative to further strive for the revision agenda to be realized immediately.